Functional overreaching: The key to peak performance during the taper? - Aubry, A.; Hausswirth, C.; Louis, J.; Coutts, A.; Le Meur, Y. (Medicine & Science in Sports & Exercise, 2014)
Purpose: The purpose of this study is to examine whether performance supercompensation during taper is maximized in endurance athletes after experiencing overreaching during an overload training (OT) period.